Tacrolimus as Single-Agent Immunotherapy and Minimal Manifestation Status in Nonthymoma Myasthenia Gravis - Weiwei Duan (Hindawi Limited, 2021)
Background. Tacrolimus is a second-line immunosuppressant in myasthenia gravis (MG) therapy, which is mainly used in combination with corticosteroids to reduce steroid dose and maintain the effect of immunotherapy. However, few studies have focused on the effect of tacrolimus as single-agent immunotherapy on achieving minimal manifestation status (MMS). Thus, this study is aimed at exploring the efficacy and influencing factors of tacrolimus as single-agent immunotherapy in MG. Methods. Clinical data of 75 nonthymoma MG patients treated with tacrolimus single-agent as initial immunotherapy were retrospectively analyzed. The therapeutic effect was evaluated by Myasthenia Gravis Foundation of America postintervention status. Clinical factors affecting the achievement of MMS and treatment reactivity of different MG subtypes were determined by Cox regression analysis. Results. Tacrolimus was generally safe, with only two patients (2.7%) switching medications due to side effects. 32% of patients had improved symptoms after 1 month of treatment. 69.2% of patients achieved MMS or better after one year. The age<39 years old, QMG score<11 points, and AChR−Ab titer<8.07 nmol/L were indicative of a favorable response, which was independent of gender, course of the disease. As for MG subtypes, ocular and seronegative MG showed better treatment sensitivity. Conclusions. Tacrolimus as single-agent immunotherapy takes effect quickly and can effectively enable nonthymoma MG patients to achieve MMS. Tacrolimus can be used alone for the initial immunotherapy of MG patients, especially for young, mild, and low antibody titer patients.